A New Genus of Ergasilidae (Copepoda: Cyclopoida) from the Gills of Astyanax fasciatus (Cuvier, 1819) (Actinopterygii: Characidae) - Narciso, Rodrigo Bravin [UNESP]; Brandão, Heleno; Perbiche-Neves, Gilmar; da Silva, Reinaldo José [UNESP] (De Gruyter, 2019)
Purpose: To describe a new genus and a new species of an ectoparasitic ergasilid (Copepoda, Ergasilidae) parasite of the red-tailed lambari, Astyanax fasciatus, from Jurumirim Reservoir (Upper Paranapanema River), São Paulo State, Brazil. Methods: The host fish were collected using multi-panel gill nets. The gill of each fish was washed and examined in a stereo microscope for copepods. The copepods found were stored in 70% ethanol, cleared in lactic acid, and mounted in Hoyer’s medium. Some specimens were dissected in glycerol medium and then each dissected part was mounted on individual slides. Results: A new genus and a new species of Ergasilidae were described herein. Duoergasilus basilongus n. gen., n. sp. differs from all other ergasilids in having the second and third pair of biramous swimming legs (P2 and P3) each with a 2-segmented endopod, and by its unique maxillary basis, resembling a whip. Conclusions: The new copepod is the first ‘four-legged’ ergasilid with all swimming legs having a 2-segmented endopod. Duoergasilus basilongus n. sp. represents the first record of a parasitic copepod on A. fasciatus in Jurumirim Reservoir, as well as its represents the first description to species level of an ergasilid infecting an Astyanax species in Brazil. A key to the 28 accepted genera of Ergasilidae is provided.
Keywords: Brazil; Ectoparasite; Freshwater; Identification key; Jurumirim; Teleostei